A comparative study of logistic regression approach and stratified classical analysis on desire for children in Bangladesh - Sarkar, Saroje Kumar; Midi, Habshah (EuroJournals, 2009)
It has been projected that the world population will reach to nine billion by 2050. This alarming growth of population is mainly driven by fertility. The fertility rates in developed countries are close to or even below the replacement levels, while the rates in the developing countries in Asia are still much higher. Bangladesh has achieved a remarkable success in family planning programs and thereby controlling population growth without much change in socio-economic conditions but yet does not reach at the replacement level fertility. This study focused on the situation regarding sex preference among the women in Bangladesh and the results suggest a higher risk of sex preference on desire for more children. Sex preference is also significant barrier of further fertility decline in the country. To find the adjusted estimate of the sex preference on desire for more children the study have utilized the logistic regression and stratified classical approaches. The sophisticated logistic regression approach provides a fast, effective and efficient estimate and test for the stratified odds ratio than those obtained from the classical approach.